On a tumor growth model with brain lactate kinetics. (12th August 2022) - Cherfils, Laurence; Gatti, Stefania; Guillevin, Carole; Miranville, Alain; Guillevin, Rémy
Abstract: Our aim in this paper is to study a mathematical model for high grade gliomas, taking into account lactates kinetics, as well as chemotherapy and antiangiogenic treatment. In particular, we prove the existence and uniqueness of biologically relevant solutions. We also perform numerical simulations based on different therapeutical situations that can be found in the literature. These simulations are consistent with what is expected in these situations.